THE CONCEPT OF ZERO (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article discusses the emergence, development, and role of the concept of "zero," which holds a significant place in the history of mathematics. It explores fascinating facts related to the discovery of zero in India and the Islamic world, as well as its introduction to Europe. Additionally, the philosophical and practical importance of zero is examined.